Development of a electrically inspired low emission microcontroller based hybrid vehicle - Ullah, Mohammad Habib; Gunawan, Teddy Surya; Sharif, Md. Raihan; Muhida, Riza (Science Publications, 2012)
Recently, influx of research afford is being concentrated in automobile engineering to develop low emission hybrid electric vehicle to reduce the greenhouse gases such as hydro-carbons, carbon monoxide, carbon dioxide, produces from the vehicle. Approach: Hybrid Electric Vehicles (HEVs) powered by electric machines and an Internal Combustion Engine (ICE) are a promising mean of reducing emissions and fuel consumption without compromising vehicle functionality and driving performances. Reduction of emission is a significant issue to save the environment from pollution that cause of many diseases in urban areas is almost entirely due to transport using fossil fuel. Although zero emission transport has not been developed and used practically yet. Results: This study introduce a control mechanism for alternative hybrid electric vehicle combination of electric motor and gasoline engine that reduce the use of fossil fuel without compromising the overall car performance. Conclusion: In this study, a microcontroller based control mechanism of HEV is introduced which consists of battery, voltage indicator, DC motor controller and battery charger.